Estudo numérico-experimental da gaseificação de pellets de bagaço de cana-de-açúcar em leito fluidizado circulante - Medeiros, Marcelo Ricardo Queiroz (2020)
This Thesis object is the development of a 3-D reactive model, multiphase flow, with multiple gaseous and solid species, with heat and mass transfer and standard turbulent k- model. The objective was to predict the syngas composition generated in a circulating fluidized bed gasifier. To achieve these objectives, some activities were done: thermogravimetric analysis (TGA) for sugarcane bagasse drying and devolatilization; experimental gasification tests in a pilot plant; and CFD simulations with Euler-Euler formulation to describe the gasification process. The used methodology were: Arrhenius parameters determination for the pellets drying and devolatilization processes through TGA experiments; and gasification experiments at 850 ° C using an equivalence ratio between 0.25 to 0.29 and a mass flow with steam between biomass ratio of 0.8 to 1.2. The proposed kinetic model contained the main reactions from literature and obtained data in this thesis. The simulations boundary conditions were the non-trivial gasification tests operation conditions. Four gasification models were investigated in this work. The obtained numerical data were compared with experimental data and literature data. The gasification model with the smallest deviation compared to preliminary experimental data was used to simulate the other gasification tests. The results show the evaluation of the interest species of the generated syngas in the gasification experiments.